Can management buffer pasture loss and fragmentation for Sami reindeer herding in Sweden? - Alessia Uboni; Birgitta Åhman; Jon Moen (Pastoralism, 2020)
Abstract Today, climate change and competing land use practices are threatening rangelands around the world and the pastoral societies that rely on them. Reindeer husbandry practised by the indigenous Sami people is an example. In Sweden, approximately 70% of the most productive lichen pastures (important in winter) has been lost, either completely or because of a reduction in forage quality, as a result of competing land use (primarily commercial forestry). The remaining pastures are small and fragmented. Yet, the number of reindeer in Sweden shows no general decline. We investigated the strategies that have allowed reindeer herders to sustain their traditional livelihood despite a substantial loss of pastures and thus natural winter forage for their reindeer. Changes in harvest strategy and herd structure may partially explain the observed dynamics, and have increased herd productivity and income, but were not primarily adopted to counteract forage loss. The introduction of supplementary feeding, modern machinery, and equipment has assisted the herders to a certain extent. However, supplementary feeding and technology are expensive. In spite of governmental support and optimized herd productivity and income, increasing costs provide low economic return. We suggest that the increased economical and psychosocial costs caused by forage and pasture losses may have strong effects on the long-term sustainability of reindeer husbandry in Sweden.